MANAJEMEN PEMBELAJARAN DI SMK NEGERI 2 SEMARANG - Thomas, Partono (Dinamika Pendidikan, 2011)
The Objective of this study is to know and analyze the planning, the teaching-learning process and the assessment in SMK Negeri 2 Semarang. The significances of this study are firstly, as a means to improve knowledge and technology especially about learning management for educational institutions, secondly, as an input for schools about learning management so the learning objectives can be conducted effectively and efficiently, thirdly as an input for related institutions, especially about learning management so the result of the study can be experienced by the society directly. This research used qualitative approach since it was a descriptive qualitative study. The techniques for collecting the data were interview, observation and documentation. The data were analyzed through data reduction, data presentation and concluding. And then triangulation was done to get the valid data. The result showed that before teaching, the teachers discuss together about planning until assessment under the control of the principal; next, the preparation by a techer including preparing the materials and media, until designing the method of teaching. After that, the teching-learning process which involves three activities; warming-up activity, main activities and cooling-down activity. And finally, the ssessment which is done during the teacjing-learning process and after learning in the form of students learning result. Moreover, for student who face difficulties in learning, the teacher gives remedial opportunity so their result can finally achieve Criteria of Minimal Score (kriteria ketuntasan minimal/KKM).